BIST, FOREIGN CAPITAL AND EXCHANGE RATE RELATIONS: 1988-2015 - Ömer Selçuk Emsen; Ensar Ağırman (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In this study, the Borsa Istanbul index, which reflects its reaction to short-term changes in the economy, has been transformed into real (RBIST) with the US dollar. RBIST with Real Exchange Rate (RER) as the short-run variables that either affect RBIST or affected by it, foreign direct investment (FDI) to GDP ratio (FDIY) and the ratio of portfolio investments to GDP (PIY) as both short and long-term indirect capital investments were taken into consideration in this study. This study which is on the relationship between these four variables covers the period from 1988 to 2015 and the data are taken on an annual basis. According to the results of the stationary survey, it was determined that while some of the series were stationary in the level and some of them were stationary in the first difference. According to the causality analysis with stationary series, one-way causal relations from RBIST to FDIY and RER to FDIY were obtained. According to this, it can be said that the real economy policies in Turkey have triggered direct foreign capital attraction and the stock market has attracted direct foreign capital as a leading indicator.